2018
DOI: 10.1007/s11356-018-2609-7
|View full text |Cite
|
Sign up to set email alerts
|

The influence of solid-liquid coefficient in the fate of pharmaceuticals and personal care products in aerobic wastewater treatment

Abstract: Wastewater treatment plants (WWTPs) are considered to be a source of environmental contamination by micropollutants, especially from pharmaceuticals and personal care products (PCPs). The pathway of those compounds during sewage treatment has been investigated, but data from real-scale WWTPs is still missing (for example, the values of the solid-liquid coefficient (K) during treatment). This paper uses the K values for some pharmaceuticals and PCPs (fenofibrate, gemfibrozil, propranolol, metoprolol, salicylic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 57 publications
0
6
0
1
Order By: Relevance
“…The biotransformation and stability of NPS in wastewater has received little attention so far and most of the WBE studies have focused on in-sample stability [ 25 , 28 ]. Furthermore, the fate of NPS and their transformation products (TPs) in wastewater treatment processes is not thoroughly investigated yet, compared to other chemicals of emerging concern (i.e., pharmaceuticals, household chemicals, personal care products, and pesticides [ 29 , 30 , 31 , 32 ]). Metabolism and biotransformation studies of NPS are of high importance and should be promoted, since there is a need to choose the most representative compounds for WBE and to detect potential overlap of other biotransformation (i.e., microbial and mammalian) routes [ 19 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…The biotransformation and stability of NPS in wastewater has received little attention so far and most of the WBE studies have focused on in-sample stability [ 25 , 28 ]. Furthermore, the fate of NPS and their transformation products (TPs) in wastewater treatment processes is not thoroughly investigated yet, compared to other chemicals of emerging concern (i.e., pharmaceuticals, household chemicals, personal care products, and pesticides [ 29 , 30 , 31 , 32 ]). Metabolism and biotransformation studies of NPS are of high importance and should be promoted, since there is a need to choose the most representative compounds for WBE and to detect potential overlap of other biotransformation (i.e., microbial and mammalian) routes [ 19 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…In BA-U samples, peak concentrations occurred at 07:00 and 15:00, while for BA-D, peak concentrations occurred between 13:00 and 15:00, and the lowest concentration was detected at 07:00. Previous studies showed that the removal of TCS in WWTP is between 30 and 80%, but the concentrations detected in the effluent are still high and could contaminate the environment [4,19]. The detection of TCS in surface waters in Brazil and in other countries is very frequent, indicating this is a ubiquitous compound.…”
Section: Resultsmentioning
confidence: 99%
“…The studies often report monitoring frequencies in surface water of a few campaigns per year [17], or even only in dry and rainy seasons [18] to assess the seasonality. In studies analyzing the effluent of WWTPs, the frequency is lower [19,20], with some such studies consisting of only a single sampling campaign [7,21].…”
Section: Introductionmentioning
confidence: 99%
“…The current concentration of pharmaceuticals released into the environment exceeds its natural capability to degrade them. The natural attenuation and detoxification of pharmaceuticals in the environment can occur through sorption, hydrolysis, photolysis, dispersion, biodegradation, dilution and, more rarely, through radioactive decomposition (Figure 1) [67][68][69][70][71][72]. Nevertheless, a review of the fate of pharmaceuticals in sewage and freshwaters suggests that hydrolysis might not have a significant role in their elimination from the environment, photodegradation and biodegradation being the processes described as more relevant in that mechanism [68].…”
Section: Pharmaceuticals In the Environmentmentioning
confidence: 99%